Reception of Carl Schmitt’s Politische Romantik - Jokubaitis, Linas (Problemos, 2016)
The aim of this article is the analysis of the reception of Carl Schmitt’s Politische Romantik. The analysis shows that during the interwar years many scholars from different fields of academic research found this work to be a very original and fruitful interpretation of the Romantic movement. Two of the most influential interpretations of Politische Romantik were published during the interwar years. According to Hugo Ball’s interpretation, Schmitt has to be understood primarily as a Catholic political philosopher. According to Karl Löwith, the German jurist is a representative of a nihilistic political thought. The analysis has in this paper shows that Ball’s interpretation has to be considered as the better one. After the Second World War Politische Romantik became a forgotten book. Even after the international rebirth of interest in Schmitt’s political thought his analysis of political romanticism has received only very little attention. Most scholars treat this work as if it were of secondary importance. It is argued that such interpretation is mistaken.